Efektivitas Program Gerakan Literasi Sekolah Dalam Meningkatkan Minat Baca Siswa di SMP Negeri 7 Medan - Geby Claudia Purba; Bengkel Bengkel; Husni Thamrin; Lina Sudarwati; Hairani Siregar (Universitas Medan Area, 2026)
This study aims to analyze the implementation of the School Literacy Movement (GLS) program and the differences in reading interest of eighth-grade students at SMP Negeri 7 Medan. The research used a mixed methods approach with a one-group pretest–posttest design. Quantitative data were obtained through a reading interest questionnaire given to 33 eighth-grade students before and after the implementation of the program, while qualitative data were obtained through observations, interviews, and documentation. Quantitative data were analyzed using the Paired Sample t-test, while qualitative data were analyzed through data reduction, data presentation, and drawing conclusions. The research results show that the implementation of GLS is carried out through 15-minute reading activities before learning, the use of reading corners, and other literacy activities involving teachers, students, and parents. The statistical test results showed an increase in the average student reading interest from 72.533 to 85.139 with a significance value of < 0.001. Thus, there is a significant difference in the reading interest of eighth-grade students before and after the implementation of the School Literacy Movement program.